Gambling Industry Strategies to Influence the Reform of State Online Monopolies: The Case of the Gambling Industry in Sweden and Finland - Sama, Thomas Babila; Hiilamo, Heikki (Critical Gambling Studies, 2024)
The aim of this qualitative study was to investigate the strategies used by the gambling industry to influence the reforming of the state online monopoly into a licensing system in Sweden in 2019, and to weaken state online monopoly in Finland. Methodologically, this study used primary data from 9 expert interviews in both countries and secondary data from prior literature, which were analyzed using thematic content analysis. The results identified five main political strategies used by the gambling industry: (1) Information, through lobbying politicians; (2) Constituency Building, through forming an alliance with interest groups; (3) Policy Substitution, through promoting alternative policies and self-regulation; (4) Legal Infringements; and (5) Regulatory Redundancy. The study concluded that the involvement of the gambling industry in policy-making influenced the change of the state online monopoly into a licensing system in Sweden in 2019 and is weakening the state online monopoly in Finland.